2017
DOI: 10.1371/journal.pone.0169826
|View full text |Cite
|
Sign up to set email alerts
|

Use of Proton-Pump Inhibitors Predicts Heart Failure and Death in Patients with Coronary Artery Disease

Abstract: ObjectivesProton-pump inhibitors (PPIs) seem to increase the incidence of cardiovascular events in patients with coronary artery disease (CAD), mainly in those using clopidogrel. We analysed the impact of PPIs on the prognosis of patients with stable CAD.MethodsWe followed 706 patients with CAD. Primary outcome was the combination of secondary outcomes. Secondary outcomes were 1) acute ischaemic events (any acute coronary syndrome, stroke, or transient ischaemic attack) and 2) heart failure (HF) or death.Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 34 publications
(41 reference statements)
0
12
0
2
Order By: Relevance
“…Daily low-dose aspirin is recommended for the prevention of cardiovascular events in patients with CAD, and PPI is recommended to prevent or treat aspirin-associated gastrointestinal injury [16][17][18] . Previous studies have reported that low-dose aspirin therapy protects against incident asthma [27][28][29] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Daily low-dose aspirin is recommended for the prevention of cardiovascular events in patients with CAD, and PPI is recommended to prevent or treat aspirin-associated gastrointestinal injury [16][17][18] . Previous studies have reported that low-dose aspirin therapy protects against incident asthma [27][28][29] .…”
Section: Discussionmentioning
confidence: 99%
“…Coronary artery disease (CAD) is one of the major cardiovascular diseases affecting the global human population 15 . Daily low-dose aspirin is recommended for the prevention of cardiovascular events in patients with CAD, and PPI is recommended to prevent or treat aspirin-associated gastrointestinal injury [16][17][18] . However, the association between PPIs use and incident asthma in patients with CAD remains unclear till now.…”
Section: Introductionmentioning
confidence: 99%
“…Dai et al 24 and others 25,26 suggested that the tendency of physicians to prescribe certain medications to patients with more severe illnesses, termed the ‘channeling bias’, is responsible for the association between PPI consumption and cardiovascular risk. This practice creates the false impression that the drugs are predisposing patients to illness because patients with certain diseases are more likely to be taking them.…”
Section: Discussionmentioning
confidence: 99%
“…68 In contrast, in a study of 42902 PPI initiators vs 3296 histamine H 2 receptor antagonist (H2RA) initiators, H2RA use was associated with lower mortality in HF patients than was PPI use. 69 In a study of 706 patients, PPI use was associated with increased HF incidence and mortality 70 ; in a study of all-cause mortality associated with taking PPIs conducted in more than 200 000 US veterans, PPI use was associated with a "small excess" of cause-specific mortality including deaths from cardiovascular disease. 71 If the positive effects we observe in mice are repeated in a large animal model, the possibility of assessing the worth of altering the gut microbiome for HF patients could be considered, perhaps with dietary modifications or fecal transplantation rather than with PPIs, given the potential health concerns.…”
Section: Discussionmentioning
confidence: 99%